Dual-trigger improves the outcomes of in vitro fertilization cycles in older patients with diminished ovarian reserve: A retrospective cohort study - Chyi-Uei Chern; Ju‐Yueh Li; Kuan‐Hao Tsui; Peng‐Hui Wang; Zhi‐Hong Wen; Li‐Te Lin (2020)
Background Dual-trigger for final oocyte maturation has been applied on the women with poor ovarian response or diminished ovarian reserve. However, the results were controversial. The Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number (POSEIDON) stratification is a set of newly established criteria for low prognosis patients. The aim of this study was to examine the effectiveness of dual-trigger for final oocyte maturation on the in vitro fertilization (IVF) outcomes of patients who fulfill the POSEIDON group 4 criteria. Methods This retrospective cohort study investigated 384 cycles fulfilling the POSEIDON group 4 criteria. The patients underwent IVF treatment using the gonadotropin-releasing hormone (GnRH) antagonist protocol. The study group contained 194 cycles that received dual-trigger (human chorionic gonadotropin [hCG] plus GnRH-agonist) for final oocyte maturation. The control group included 114 cycles where final oocyte maturation was performed with only hCG. Baseline characteristics and cycle parameters, as well as IVF outcomes of both groups were compared. Results Baseline characteristics were similar between the dual trigger group and the control group. In terms of IVF outcomes, the dual trigger group demonstrated significantly higher number of retrieved oocytes, metaphase II oocytes, fertilized oocytes, day-3 embryos, and top-quality day-3 embryos. A statistically significant improvement in clinical pregnancy rate and live birth rate was also observed in the dual trigger group. Conclusions Our data suggests that dual trigger for final oocyte maturation might improve clinical pregnancy rates and live birth rates of IVF cycles in patients fulfilling the POSEIDON group 4 criteria.